The Impact of Shuttle Run Training on Sprint 100 Meters for Elementary School Students (9-10 Year Age Category) - Pradana, Randy (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2022)
The purpose of the study.The background of this research is that the results of the sprint run conducted by Pahlawan Elementary School students, Bangkinang Kota are not optimal and are not appropriate in their implementation. Materials and methods. Research Methods This research uses a pre-experimental method with One Group, namely Pre-test and Post-test Design. The data collection technique was purposive sampling with inclusion and exclusion criteria. Data analysis in this study used the Wilcoxon test, Paired Sample T-test. Results. Research results based on the statistical output of